P373 Daily aspirin use does not impact clinical outcomes in patients with inflammatory bowel disease. (16th January 2018) - Patel, P; Gao, G; Gulotta, G; Rubin, D T; Dalal, S; Cohen, R D; Sakuraba, A; Pekow, J
Abstract: Background: Aspirin is a non-steroidal anti-inflammatory drug (NSAID) which is recommended for primary or secondary prevention of coronary artery disease (CAD). Although several studies have associated the use of other NSAIDS with disease flares in patients with inflammatory bowel disease (IBD), little is known about the impact of daily aspirin use on clinical outcomes in patients with IBD. Methods: We conducted a retrospective analysis of a prospectively collected registry of patients with IBD from May 2008 to June 2015. Patients in the registry with daily aspirin use were matched 1:4 to controls by age, sex, disease, disease location and presence of cardiac co-morbidity. Patients with at least 18 months of follow-up were included in the analysis. The primary outcomes of interest were an IBD-related hospitalisation, IBD-related surgery, and requiring corticosteroids during the follow-up period. To test for an association between each outcome and the use of aspirin while controlling for co-variables, we used a zero-inflated Poisson regression model evaluating for a binary association of each outcome with aspirin use. Results: A total of 764 patients with IBD were included in the analysis, of which 174 patients were taking ASA. Of these patients, 611patients had Crohn's disease. The median age was 61 years, and the median length of follow-up in this cohort was 54 months (IQR 38–79). 74% ( n = 128) patients were on 81 mg of ASA and the median duration of ASA use was 45 months (IQR 30–61). There was no statistical difference in age, gender, diagnosis (Crohn's vs. ulcerative colitis), disease duration, Charlson Comorbidity index, smoking status, medication use, or baseline C-reactive protein between groups. After controlling for co-variables and length of follow-up, aspirin use was not associated with a risk of being hospitalised for an IBD-related complication (Poisson regression estimate (PRE) = −0.38, p = 0.12), corticosteroid use (PRE = 0.08, p = 0.70), or having an IBD-related surgery (PRE = 0.01, p = 0.96). There was no association with these outcomes and aspirin use in sub-analyses of subjects with Crohn's disease or ulcerative colitis. In contrast, younger age, biologic use, cardiac comorbidities, and an elevated C-reactive protein at baseline were associated with all three outcomes. Conclusions: Aspirin use did not impact clinical outcomes in patients with IBD. Although the effect of aspirin use on mucosal inflammation was not directly assessed in this study, these findings support the safety of daily aspirin use in this population.